The History of the Kinship Group of Kuzhuget from the Barun-Khemchik District of Tuva - Kuzhuget, Shenne Yu. (The New Research of Tuva, 2021)
The article presents an example of a study of the restoration of the relations between Tuvan kin groups whose history in the 20th century was turbulent and full of breaks in family ties. The author tells the story of her kin group of Kuzhuget on the side of her mother who was native to the village of Khondelen in the Barun-Khemchik district. The family tree of the kin group of Kuzhuget is presented and the facts of adoption are noted, as well as the consequences of passportization in Tuva in the 1940s.The author in particular discusses the issue of the internal migration (within Tuva) among the members of the kinship group. Today the relatives live mainly in the Barun-Khemchik and Tandinsky districts of Tuva. This has had a certain influence on the maintenance of family ties.The article examines the issues of the strengthening of relations (through online communication) and also notes the role of ancestral rites which are conducted by the kinship groups in the two districts.
Keywords: Tuvans; history of Tuva; passportization; lineage group; kinship group; family rite; family tree; Kuzhuget; Khomushku